Screening and Characterization of New IAcetobacter/I Ifabarum/I and IAcetobacter/I Ipasteurianus/I Strains with High Ethanol–Thermo Tolerance and the Optimization of Acetic Acid Production - El-Askri, Taoufik; Yatim, Meriem; Sehli, Youness; Rahou, Abdelilah; Belhaj, Abdelhaq; Castro, Remedios; Durán-Guerrero, Enrique; Hafidi, Majida; Zouhair, Rachid (Microorganisms (Basel), 2022)
The production of vinegar on an industrial scale from different raw materials is subject to constraints, notably the low tolerance of acetic acid bacteria (AAB) to high temperatures and high ethanol concentrations. In this study, we used 25 samples of different fruits from seven Moroccan biotopes with arid and semi-arid environmental conditions as a basic substrate to isolate thermo- and ethanol-tolerant AAB strains. The isolation and morphological, biochemical and metabolic characterization of these bacteria allowed us to isolate a total number of 400 strains with characters similar to AAB, of which six strains (FAGD1, FAGD10, FAGD18 and GCM2, GCM4, GCM15) were found to be mobile and immobile Gram-negative bacteria with ellipsoidal rod-shaped colonies that clustered in pairs and in isolated chains. These strains are capable of producing acetic acid from ethanol, growing on peptone and oxidizing acetate to CO[sub.2] and H[sub.2] O. Strains FAGD1, FAGD10 and FAGD18 show negative growth on YPG medium containing D-glucose > 30%, while strains GCM2, GCM4 and GCM15 show positive growth. These six strains stand out on CARR indicator medium as isolates of the genus Acetobacter ssp. Analysis of 16S rDNA gene sequencing allowed us to differentiate these strains as Acetobacter fabarum and Acetobacter pasteurianus. The study of the tolerance of these six isolates towards pH showed that most of the six strains are unable to grow at pH 3 and pH 9, with an ideal pH of 5. The behavior of the six strains at different concentrations of ethanol shows an optimal production of acetic acid after incubation at concentrations between 6% and 8% (v/v) of ethanol. All six strains tolerated an ethanol concentration of 16% (v/v). The resistance of the strains to acetic acid differs between the species of AAB. The optimum acetic acid production is obtained at a concentration of 1% (v/v) for the strains of FAGD1, FAGD10 and FAGD18, and 3% (v/v) for GCM2, GCM4 and GCM15. These strains are able to tolerate an acetic acid concentration of up to 6% (v/v). The production kinetics of the six strains show the highest levels of growth and acetic acid production at 30 °C. This rate of growth and acetic acid production is high at 35 °C, 37 °C and 40 °C. Above 40 °C, the production of acid is reduced. All six strains continue to produce acetic acid, even at high temperatures up to 48 °C. These strains can be used in the vinegar production industry to minimize the load on cooling systems, especially in countries with high summer temperatures.